'International chiefs': chieftaincy, rituals and the reproduction of transborder Ewe ethnic communities on the Ghana–Togo boundary. (17th July 2018) - Adotey, Edem
Abstract: The issue of 'alien' voters in Ghana's electoral politics since the return to multiparty democracy in 1992 points to tensions between local/ethnic identities in culturally demarcated spaces and national identity/citizenship promoted by states. Focusing on the two Ewe-speaking communities of Nyive and Edzi, this article examines the legacies of partition in the aftermath of World War One, when the British and French split the former German colony of Togo between themselves and established new administrations under international oversight. It argues that relationships have changed, specifically from political hegemony to largely ritual practices, and that, though distinct, the two are co-determining. The salience or legitimacy of political authority is sustained by ritual authority, and chiefly authorities invest in these rituals to maintain political authority. These shared ritual practices are important, as they are mobilized to promote a sense of belonging among Ewe communities that straddle state boundaries. This is evident in the phenomenon of 'international chiefs', as expressed in continued allegiances of village chiefs in Ghana to senior/paramount chiefs in Togo. Résumé: La question des électeurs « étrangers » dans la politique électorale du Ghana depuis le retour à la démocratie multipartite en 1992 révèle des tensions entre identités locales/ethniques au sein d'espaces culturellement démarqués et de l'identité nationale/citoyenneté promue par les États. À travers les deux communautés ewephones de Nyive et d'Edzi, cet article examine les séquelles de la partition au lendemain de la Première Guerre mondiale, lorsque les Britanniques et les Français se sont partagés l'ancienne colonie allemande du Togo et ont établi de nouvelles administrations sous supervision internationale. Il soutient que les relations ont changé en passant d'une hégémonie politique à des pratiques essentiellement rituelles et que les deux, bien que distinctes, sont codéterminantes. La prépondérance ou la légitimité de l'autorité politique est entretenue par l'autorité rituelle, et l'autorité des chefs investit dans ces rituels pour maintenir l'autorité politique. Ces pratiques rituelles partagées sont importantes car elles sont mobilisées pour promouvoir un sentiment d'appartenance parmi les communautés ewe qui vivent de part et d'autre de la frontière de l'État. C'est manifeste dans le phénomène des « chefs internationaux », tel qu'il s'exprime dans le maintien d'allégeances de chefs de villages du Ghana à des chefs supérieurs/suprêmes au Togo.